Identification of Type 2 Diabetes Mellitus Risk Factors in Urban Communities Of Archipelago and Mining Regions: Stakeholders Perspective - Layal, Kamalia; Azmy, Restu Amalia; Zulkifli; Suherman (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Bangka Belitung is an archipelagic region and the world's second-largest tin producer. Communities in coastal and mining areas face health issues related to behavior, individual characteristics, and cultural factors influencing disease patterns. One prevalent disease among urban populations in Bangka Belitung is diabetes mellitus. This study aims to explore the risk factors of diabetes mellitus in urban communities in Bangka Belitung from the stakeholders' perspective. This research employed a qualitative exploratory approach conducted in Pangkalpinang city. Data were collected through in-depth interviews with participants, including eight heads of public health centers, one head of the health department, one chairperson of the Indonesian Medical Association (IDI), nine patients, and nine family members of patients across nine public health center service areas in Pangkalpinang city. Data were analyzed using thematic analysis. The study identified three main themes: (1) Lifestyle, (2) Social, economic, and environmental factors, and (3) Cognitive psychology. These factors contribute to the high prevalence of type 2 diabetes mellitus (T2DM) in urban communities in the Bangka Belitung archipelago. Comprehensive knowledge and understanding of T2DM are essential to implement effective prevention and intervention strategies to control T2DM cases in urban communities in this archipelagic and mining region.